Accounting in central and eastern Europe - Albu, Catalin Nicolae; Mustata, Razvan V. (Emerald, 2013)
Countries in Central and Eastern Europe (CEE), most of them former components of the communist bloc, have suffered diverse influences over time. Historically, the advent of communism in the 1950s has stopped the economic and political development of these countries. Its fall during the late 1980s and early 1990s triggered severe changes in the economic and social environment, with profound consequences on the countries accounting and business models. The accounting regulatory process of these countries has mostly been a public one, although some countries also involved private sector and professional bodies. With economic and political reforms these countries are now reforming their accounting systems with for example the adoption of International Accounting Standards/International Financial Reporting Standards (IFRS). Additionally, the CEE countries political will to join the European Union compelled the regulators to ensure a high level of harmonization with the European Directives. This volume present theoretical and empirical papers that will further our understanding of accounting issues in CEE countries.
Includes index.
Keywords: elektronické knihy; electronic books; Accounting -- Europe Central -- History -- 20th century.; Accounting -- Europe Eastern -- History -- 20th century.